Digitization of the oldest botanical collection in Ukraine (LW Herbarium): a case study - Tasenkevich, Lydia; Skrypets, Krystyna; Seniv, Maria; Khmil, Tetiana (Biodiversity: Research and Conservation, 2024)
Digitization of natural collections has become very important among all other preservation tasks. One of the ways of non-destructive examination of herbarium specimens is the study of their scanned digital images or photocopies, which makes it possible to reduce mechanical and other influences on specimens. Reconsidering the importance of collections’ digitization became particularly relevant on 24 February 2022, with the start of the last Russian invasion and due to the destruction or severe damage of many of them in the occupied territories. There was concern about the need and urgency to preserve, at least virtually, the most valuable assets of the LW Herbarium of Ivan Franko National University of Lviv. Currently, the digitization process includes 2 collections from the 19th century: (1) the most complete of all existing herbaria of vascular plants from the Southern Carpathians and Transylvania, collected by Dr Ferdinand Schur – an Austrian pharmacist and botanist; and (2) collection of one of the first researchers of bryophytes in South Africa – Antoni Rehman, then Professor of Jan Kazimierz University in Lwów (now Lviv). Both collections contain many nomenclatural types. Out of 7633 herbarium sheets from F. Schur’s collection, more than 2700 have been digitized, and 380 representatives of the family Labiatae are published in volume I of the Atlas of his collection. The digitization of the South African mosses collected by A. Rehman began in 2023. So far, 584 packets have been digitized.